The method of increasing the immunity of communication systems - Mahdi, Qasim Abbood (Національний технічний університет "Харківський політехнічний інститут", 2019)
Nowadays, due to a severe shortage of radio resources of communication systems, which is caused by an increase in the number of subscribers of cellular communication systems, an increase in demand for information resources, which in turn leads to the search for new technological approaches to its solution. The analysis of well-known scientific works carried out in the article showed that the technology of orthogonal frequency multiplexing almost completely exhausted the possibility of its improvement. One of the ways to improve the efficiency of radio resource use of communicationsystems is using spectrally effective signals. This article has developed a methodology for improving the noise immunity of communication systems. The essence of this methodis to switch the modes of communication in the session mode, depending on the signal- interference situation in the channel, with the subsequent adjustment of the parameters of the communication channel by selecting the optimal signal-code structures. In the course of the research, the main provisions of the theory of communication, the theory of signal-code structures, the theory of noise immunity, as well as general scientific methods such as analysis and synthesis were used. A distinctive feature of this methodfrom the known,which determines its novelty are:the possibility of changing themode of operation in the session mode; the modes of operation of this technique are signals with orthogonal frequency multiplexing and spectral-effective signals. The proposed technique provides 15–18% more noise immunity compared with the known methods of generating spectral-effective signals, but 10–12% less noise immunity compared to the orthogonal signals.

На даний час у зв'язку спостерігається жорсткий дефіцит радіоресурсу систем зв'язку, який викликаний збільшенням кількості абонентів систем стільникового зв'язку, зростанням попиту на інформаційні ресурси, що в свою чергу призводить до пошуку нових технологічних підходів до її вирішення. Проведений в статті аналіз відомих наукових праць показав, що технологія ортогонального частотного мультиплексування фактично повністю вичерпала можливість свого поліпшення. Одним із шляхів підвищення ефективності використання радіоресурсу систем зв'язку є перехід до використання спектрально-ефективних сигналів. В даній статті проведено розробку методики підвищення завадозахищеності систем зв'язку. Сутність даної методики полягає в перемиканні режимів роботи засобів зв'язку в режимі ведення сеансу зв'язку в залежності від сигнально-завадової обстановки в каналі, з подальшим корегуванням параметрів каналу зв'язку за рахунок вибору оптимальних сигнально-кодових конструкцій. В ході проведеного дослідження були використані основні положення теорії зв'язку, теорії сигнально-кодових конструкцій, теорії завадозахищеності, а також загальнонаукові методи, такі як аналіз і синтез. Відмінними особливостями даної методики від відомих, що визначають її новизну, є такі: можливість зміни режиму роботи в режимі сеансу зв'язку; режимами роботи даної методики є сигнали з ортогональним частотним мультипексуванням і спектрально- ефективні сигнали. Запропонована методика забезпечує на 15-18% більшу завадозахищеність в порівнянні з відомими методиками формування спектрально-ефективних сигналів, але на 10- 12% меншу завадозахищеність в порівнянні з ортогональними сигналами.
Методика підвищення завадозахищеності систем зв'язку
Keywords: radio resource; spectral-effective signals; orthogonal frequency multiplexing; радіоресурс; спектрально-ефективні сигнали; ортогональне частотне мультиплексування